Pengaruh Work Life Balance dan Strategi Kepemimpinan terhadap Kinerja Pegawai di Puskesmas Tebing Gerinting pada Era New Normal - M. Rifki Faizal; Sably Aliya (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to determine whether Work Life Balance and leadership strategies affect the performance of Tebing Gerinting Public Health Center employees. The sample in this study were 41 respondents who were permanent employees. The sampling method used by the researcher is Random Sampling. This type of research is quantitative research using multiple linear regression analysis techniques which are processed using the SPSS application The results in this study are: 1.) Work Life Balance variable has a T count of 10,900 with a significant level of 0.000 < 0.05, this indicates that H0 is rejected and H1 is accepted because t count > t table (10.900 > 1.677). This means that Work Life Balance has a significant effect on the performance of Tebing Gerinting Health Center employees. 2.) The leadership strategy variable has a T count of 6.272 with a significant level of 0.000 < 0.05, this indicates that Ho is rejected and H2 is accepted because t count > t table (6.272> 1.677). This means that the leadership strategy has a significant effect on the performance of the Tebing Gerinting Health Center employees. 3.) that the F value is 329.532 with a significance level of 0.000, because the significance level is 0.05, this regression model can be used for employee performance. This means that f count > f table (329.532>2.79) the results state that Work Life Balance and leadership strategies have a direct (simultaneous) effect on the performance of Tebing Gerinting Health Center employees. Keywords: Work Life Balancem leadership stategy, Puskesmas Tebing Gerinting